Determinants of MSME Workers’ Well-Being: A Structural Equation Modeling Approach - Desfitrina; Zulfadhli (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in Indonesia’s economic growth and social development by creating jobs, reducing poverty, and fostering an inclusive and resilient society. The primary aim of this research is to empirically examine the contribution of human, social, physical, financial, and natural capital towards enhancing the well-being of MSME workers. With a quantitative method, data from 250 respondents were collected by using a structured questionnaire based on measurements on a 1–5 Likert scale. The analysis was carried out using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings reveal that all five types of capital have a positive and significant impact on the well-being of workers, with human capital and financial capital as the most dominant contributors, followed by social capital, physical capital, and natural capital. The model accounts for 67% of the variance in workers’ well-being with high predictive validity. These results validate that fostering welfare among MSMEs needs holistic solutions with individual, financial, social, infrastructure, and environmental aspects. The study offers actionable suggestions to policymakers, MSME managers, and development agencies to enhance holistic capital-based programs to foster employees’ welfare and productivity.